Preparation, characterization, and property evaluation of Hericium erinaceus peptide–calcium chelate - Gu, Haofeng; Liang, Lei; Kang, Yongning; Yu, Rongmiao; Wang, Jiahao; Fan, Dan (Frontiers in Nutrition, 2024)
Recently, owing to the good calcium bioavailability, peptide-calcium chelates made of various foods have been emerging. Hericium erinaceus, an edible fungus, is rich in proteins with high proportion of calcium-binding amino acids. Thus, mushrooms serves as a good source to prepare peptide-calcium chelates. Herein, the conditions for hydrolyzing Hericium erinaceus peptides (HP) with good calcium-binding rate (CBR) were investigated, followed by the optimization of HP-calcium chelate (HP-Ca) preparation. Further, the structure of the new chelates was characterized along with the evaluation of gastrointestinal stability and calcium absorption. Papain and hydrolysis time of 2 h were selected for preparing Hericium erinaceus peptides, and the conditions (pH 8.5, temperature 55℃, time 40 min and mass ratio of peptide/CaCl 2 4:1) were optimal to prepare HP-Ca. Under this condition, the chelates contained 6.79±0.13% of calcium. The morphology and energy disperse spectroscopy (EDS) analysis showed that HP-Ca was loose and porous with obvious calcium element signal. The ultraviolet-visible (UV) absorption and fourier transform infrared spectroscopy (FT-IR) analysis indicated that calcium possibly chelates to HP via interaction with free -COO-from acidic amino acids and C=O from amide. HP-Ca displayed good stabilities against stimulated gastrointestinal digestion.Moreover, HP-Ca significantly improved the calcium absorption by Caco-2 epithelial cells. Thus, HP-Ca is a promising Ca-supplement with high calcium bioavailability.